Socio-Cultural Aspects of Teaching Foreign Languages in The Faculty of Languages and Arts, State University of Jakarta - Ekowati, Sri Harini; P, Indira Kusuma (International Journal of Active Learning, 2018)
This study aims to identify the social and cultural aspects in the French and German textbooks. It stands to reason that learning a foreign language inevitably involves socio-cultural aspects as language does not stand alone but must be related to the context. When teachers teach foreign language at the same time they also introduce its socio-cultural aspects. In consequence, textbooks should contain all the socio-cultural aspects of the language to be learnt. CECRL, a theory derived from Didier, is employed to determine the socio-cultural aspects in the French and German textbooks. There are seven aspects of socio-cultural by Didier but the writers will only use six aspects, they are: La vie quotidienne, Les conditions de vie, les relations interpersonnelles, valeurs, croyences, et comportements, savoir-vivre, comportements rituels. The analysis of two textbooks show that the textbooks contain six aspects of socio- cultural having daily lives as the most dominant.